Are leaders with postgraduate degrees perceived to be more transformational? A quasi-experimental field study. Issue 2 (12th February 2019) - Mendelson, Morris; Alam, Jasmine; Cunningham, Chris; Totton, Adam; Smith, Carrie
Abstract : Purpose: Transformational leadership has been shown to have a positive impact on a host of employee level and organizational performance indicators. However, little research has sought to understand some of the antecedents of this style of leadership. The purpose of this paper is to examine the link between having a post-secondary education and perceptions of transformational leadership. Design/methodology/approach: Data were collected from two surveys issued in a mid-sized energy company located on the eastern seaboard of North America. One-way ANOVA comparing employees' perceptions of transformational leadership exhibited by their supervisors that either did or did not have a post-graduate degree demonstrated a strong, positive relationship between the attainment of a Master's degree and perceived levels of transformational leadership qualities. Findings: The findings of this quasi-experimental field study demonstrated a strong, positive relationship between the attainment of a Master's degree and perceived levels of transformational leadership qualities. Originality/value: This study is the first of its kind to demonstrate that more educated managers are generally perceived to be more transformational in their leadership style.